The phylogenetic analysis of tetraspanins projects the evolution of cell–cell interactions from unicellular to multicellular organisms - Huang, Shengfeng; Yuan, Shaochun; Dong, Meiling; Su, Jing; Yu, Cuiling; Shen, Yang; Xie, Xiaojin; Yu, Yanhong; Yu, Xuesong; Chen, Shangwu; Zhang, Shicui; Pontarotti, Pierre; et al. (Genomics (San Diego, Calif.), 2005)
In animals, the tetraspanins are a large superfamily of membrane proteins that play important roles in organizing various cell–cell and matrix–cell interactions and signal pathways based on such interactions. However, their origin and evolution largely remain elusive and most of the family's members are functionally unknown or less known due to difficulties of study, such as functional redundancy. In this study, we rebuilt the family's phylogeny with sequences retrieved from online databases and our cDNA library of amphioxus. We reveal that, in addition to in metazoans, various tetraspanins are extensively expressed in protozoan amoebae, fungi, and plants. We also discuss the structural evolution of tetraspanin's major extracellular domain and the relation between tetraspanin's duplication and functional redundancy. Finally, we elucidate the coevolution of tetraspanins and eukaryotes and suggest that tetraspanins play important roles in the unicell-to-multicell transition. In short, the study of tetraspanin in a phylogenetic context helps us understand the evolution of intercellular interactions.